2008
DOI: 10.1007/s10457-008-9174-x
|View full text |Cite
|
Sign up to set email alerts
|

Soil water competition in a temperate hedgerow agroforestry system in South Africa

Abstract: An on-farm trial was conducted to determine dry matter production of four fodder tree species and their effect on soil water and maize production. The trees were planted in rows intercropped with maize. The four tree species selected were Acacia karroo Hayne (indigenous fodder tree), Leucaena leucocephala (Lam.) De Wit (nitrogen fixing), Morus alba L. (fodder and fruit), and Gleditsia triacanthos L. (fodder and fuel). Volumetric soil water was measured in the upper 0.3 m of soil in each row of the trial using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…Note that this is not an exhaustive list of AF tree species useful to South Africa. Everson et al (2009) conducted an on-farm study in the Upper Thukela region of KwaZuluNatal to determine dry matter production for fodder tree species and their effect on soil water and maize production.…”
Section: Af In South Africamentioning
confidence: 99%
“…Note that this is not an exhaustive list of AF tree species useful to South Africa. Everson et al (2009) conducted an on-farm study in the Upper Thukela region of KwaZuluNatal to determine dry matter production for fodder tree species and their effect on soil water and maize production.…”
Section: Af In South Africamentioning
confidence: 99%
“…The former was notable for green manure trees and fallowing, which is often associated with loss of a growing season and this will have especially large impact where there is only one short growing season (BĂŒnemann et al 2004). Yields can also be reduced if trees compete with the crops for nutrients, water and light; a phenomenon common when the density of trees is high (Everson et al 2009), and in close proximity to crops (Jama et al 1995(Jama et al , 2000Boffa et al 2000). Certain tree species are considered competitive and provide too much shading when grown together with crops, and this may reduce yields (Mathuva et al 1998;Bayala et al 2002;Gaafar et al 2006).…”
Section: Crop Yieldmentioning
confidence: 99%
“…crops, such as cocoa (Isaac et al 2007), chilli pepper, millet (Kho et al 2001) and coffee. In studies where microclimatic conditions were reporting negative effects in tree-crop systems, it was mainly due to reduced photosynthetically active radiation in semi-arid zones (McIntyre et al 1997;Ong et al 2000;Bayala et al 2002;Everson et al 2009), higher relative humidity and lower air temperature compared to monoculture in sub-humid zones (Koech & Whitbread 2006;Schroth, Balle, et al 1995). This resulted in reduced crop yields (McIntyre et al 1997;Everson et al 2009) and increased pest infestation (Koech & Whitbread 2006;Schroth, Balle, et al 1995).…”
Section: Microclimatementioning
confidence: 99%
“…Belowground interaction is affected by several biotic and abiotic factors such as soil resources availability, root characteristics, climatic conditions, and phenology (Ong et al, 1991;Jose et al, 2004) and could result in various outcomes in terms of understory growth. Some studies have observed favorable soil water conditions for understory growth in agroforestry because of hydraulic lift by trees (Emerman & Dawson, 1996;Hirota et al, 2004), while many others have reported crop yield reduction due to competition for water (Gillespie et al, 2000;Jose et al, 2000a;Miller & Pallardy, 2001;Livesley et al, 2004;Everson et al, 2009;Sudmeyer & Hall, 2015). Roots of pine trees and switchgrass could share some soil space despite the presence of 1.5-m-wide buffer between the switchgrass alley and tree row.…”
Section: Belowground Tree-grass Interactionsmentioning
confidence: 99%